Le Pavillon de la sardine, un cas de recyclage insulaire - Manuel Tardits (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This text describes the pavilion and garden project on the island of Ibuki, which is located in the Seto Inland Sea in Japan. Constructed in 2016 as part of the Setouchi Triennale, it was built with ecological construction practices, using only recycled and locally sourced resources from the island.